The Students (Mahasantri) of Ma’had Aly As’adiyah Perception in Sengkang Regarding The Trustworthiness in The Quran - Marlinda Marlinda; Darmawati Darmawati; Muhsin Mahfudz (International Journal of Islamic Studies, 2023)
This research aims to determine the perception of MA'HA Santri (Students) at Al-Aly As'adiyah Islamic Boarding School in Sengkang regarding trustworthiness in the Quran. The research objective is to understand the perception of MA'HA Santri at Al-Aly As'adiyah Sengkang regarding trustworthiness in the Quran, categorizing this study as qualitative field research. Field research uses a contextual and comprehensive approach to explore the meanings, definitions, understanding, events, and lives of individuals directly or indirectly involved in the research subject. According to the students of Ma’had Aly As’adiyah Sengkang, the implementation of trustworthiness has been carried out effectively. The execution of these qualities aligns with the indicators in this study, namely responsibility, transparency, and keeping promises. The students (Mahasantri) at Ma'had Aly As'adiyah Sengkang have applied these indicators in their teaching processes at the campus to achieve quality learning. Implementing trustworthiness in learning by the students at Al-Aly As'adiyah Sengkang can produce high-quality outcomes. Quality learning can enhance knowledge for the future, benefiting oneself and others. However, some MA'HA Santri may still need to improve their trustworthiness in their daily lives.